Surface states in noncentrosymmetric superconductor BiPd. Issue 1 (1st March 2022) - Pramanik, Arindam; Pandeya, Ram Prakash; Vyalikh, Denis V; Generalov, Alexander; Moras, Paolo; Kundu, Asish K; Sheverdyaeva, Polina M; Carbone, Carlo; Joshi, Bhanu; Thamizhavel, A; Ramakrishnan, S; Maiti, Kalobaran
Abstract: BiPd is a noncentrosymmetric superconductor with Dirac-like surface states on both (010) and ( 0 1 ¯ 0 ) faces. The Dirac cone on (010) surface is intense and appears at 0.66 eV binding energy. These states have drawn much attention due to contradictory reports on dimensionality and the momentum of these Dirac fermions. We have studied the properties of these Dirac fermions using varied photon energies and different experimental conditions. The behavior of the Dirac cone is found to be two-dimensional. In addition, we found few more surface states appearing at higher binding energies compared to the Dirac cone.